Experimental mixture design as a tool to optimize the growth of various Ganoderma species cultivated on media with different sugars. Issue 1 (2nd January 2016) - Goh, Yit Kheng; Marzuki, Nurul Fadhilah; Tan, Suet Yee; Tan, Swee Sian; Tung, Hun Jiat; Goh, You Keng; Goh, Kah Joo
ABSTRACT: The influence of different medium components (glucose, sucrose, and fructose) on the growth of different Ganoderma isolates and species was investigated using mixture design. Ten sugar combinations based on three simple sugars were generated with two different concentrations, namely 3.3% and 16.7%, which represented low and high sugar levels, respectively. The media were adjusted to either pH 5 or 8. Ganoderma isolates (two G. boninense from oil palm, one Ganoderma species from coconut palm, G. lingzhi, and G. australe from tower tree) grew faster at pH 8. Ganoderma lingzhi proliferated at the slowest rate compared to all other tested Ganoderma species in all the media studied. However, G. boninense isolates grew the fastest. Different Ganoderma species were found to have different sugar preferences. This study illustrated that the mixture design can be used to determine the optimal combinations of sugar or other nutrient/chemical components of media for fungal growth.